The triads as business - Chu, Yiu Kong, 1962- (Routledge studies in the modern history of Asia, 2000)
Based on interviews with ex members and triad victims, police from Hong Kong, mainland China and Europe, and documentary evidence, The Triads as Business gives a compelling picture of the triads as part of a wider society.